Cartilage Tissue Engineering Using Mesenchymal Stem Cells and 3D Chitosan Scaffolds – In vitro and in vivo Assays - Breyner, Natália Martins; Zonari, Alessandra Arcoverde; Carvalho, Juliana Lott; Gomide, Viviane Silva; Gomes, Dawidson; Góes, Alfredo Miranda (IntechOpen, 2011)
None